Psychometric properties and factorial structure of the Spanish version of the HLS-EU-Q16 questionary in Venezuelan adults - Judith Francisco-Pérez; Víctor López-Guerra; Gabriel Ortíz; Angélica Rojas; Carmen Martínez; Ronald Serrano (PLoS ONE, 2025)
Health literacy is a variable determined by personal skills and resources for information management and health-related decision making. Studies have shown that it positively influences health maintenance and disease prevention. To contribute to the lack of validated and adapted instruments in Latin America, this study aimed to analyze the psychometric properties of the HLS-EU-Q16 questionnaire short version in Spanish, in Venezuelan adult population. A non-probabilistic intentional sample of 972 (mean age 41.55 years, SD = 15.64; 67.5% female) was surveyed using a cross-sectional design. Data analysis included exploratory (EFA) and confirmatory factor analysis (CFA), factorial invariance, assessment of internal consistency and group contrasting method according to educational level and economic capacity. The three-factor model showed the best fit to the data (X2/df = 1.52; CFI = .990; TLI = .988; SRMR = .056; RMSEA = .033) and such model remained invariant across sex. The internal consistency was adequate, with Alpha and Omega coefficients for the total scale (α = .88, ω = .88) and three factors: health care (α = .83, ω = .81), disease prevention (α = .73, ω = .73) and health promotion (α = .88, ω = .88). The results indicate that people with postgraduate studies report higher levels of health literacy and people who have borrowed money to buy food or medicines, who have stopped seeing their doctor or taking medicines due to lack of money have low levels of health literacy. The HLS-EU-Q16 questionnaire adapted to Venezuela is reliable, valid and easy to apply. Hence, it will be useful for measuring health literacy and generating preventive programs.